ANALISIS KINERJA KEUANGAN PERUSAHAAN PADA PT GOTO GOJEK TOKOPEDIA TBK SETELAH MERGER DAN AKUISISI - Annisa Cahyanita; Damayanti Damayanti; Depita Anggraini (Soedirman Accounting, Auditing and Public Sector Journal, 2026)
This study aims to analyze whether there is an improvement in the financial performance of PT GOTO Gojek Tokopedia Tbk after the merger and acquisition during the period 2021–2024 using financial ratios. This research employs a descriptive quantitative approach and does not apply sampling techniques, as the object of analysis is limited to a single company. However, data collection was conducted intensively through the documentation of PT GOTO Gojek Tokopedia Tbk's financial reports from 2021 to 2024, all of which are secondary data. Overall, the company's financial performance did not show a significant improvement post-merger and acquisition. Liquidity ratios were above the industry average but were not accompanied by operational efficiency. Solvency ratios indicated a stable capital structure, yet earnings coverage ratios remained weak. Profitability ratios were consistently below industry standards. Meanwhile, activity ratios remained below the industry average, although improvements were observed in Inventory Turnover and Fixed Assets Turnover after the 2023 acquisition. These findings suggest that the merger and acquisition have not been able to drive a comprehensive improvement in financial performance.